1979
DOI: 10.2135/cropsci1979.0011183x001900010005x
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting Pattern in Narrow‐Row Cotton1

Abstract: Previous research with narrow‐row cotton (Gossypium hirsutum L.) has concentrated on end‐of‐season effects on yield and fiber characteristics with little attention given to seasonal fruiting patterns. Our objective was to monitor the seasonal fruiting pattern of cotton planted at various combinations of row spacings and plant densities. ‘Deltapine 16’ was grown 3 years on one or two rows per beds that were either 76 or 102 cm from center to center with densities of 7.4, 14.8, and 22.2 plants/m2. The plots were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…but heavier fruit production of individual plants, while fruiting site production, fruit retention and boll weight were reduced as population density increased Bednarz et al, 2000;Jones and Wells, 1997). Higher plant densities also produced longer sympodial and monopodial plastocrons (Kerby et al, 1990;Kerby and Buxton, 1978) and longer boll maturation period (Buxton et al, 1979;Galanopoulou-Sendouka et al, 1980). These combined effects resulted in fewer bolls and less seedcotton on a per-plant basis, suggesting that yield stability across a range of population densities is achieved through manipulation of boll occurrence and boll weight under extensive management (Bednarz et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…but heavier fruit production of individual plants, while fruiting site production, fruit retention and boll weight were reduced as population density increased Bednarz et al, 2000;Jones and Wells, 1997). Higher plant densities also produced longer sympodial and monopodial plastocrons (Kerby et al, 1990;Kerby and Buxton, 1978) and longer boll maturation period (Buxton et al, 1979;Galanopoulou-Sendouka et al, 1980). These combined effects resulted in fewer bolls and less seedcotton on a per-plant basis, suggesting that yield stability across a range of population densities is achieved through manipulation of boll occurrence and boll weight under extensive management (Bednarz et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Plant population density is inversely related to mainstem node number and monopodial branch number (Jones and Wells, 1997;Fowler and Ray, 1977;Buxton et al, 1979). Decreased plant density resulted in greater fruiting site production and fruit retention http://dx.doi.org/10.1016/j.fcr.2015.06.008 0378-4290/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, devido aos baixos preços internacionais da pluma e ao alto custo de produção, os cotonicultores têm buscado alternativas para viabilizar a continuidade no sistema. Uma dessas alternativas é a utilização de espaçamentos reduzidos, para redução do ciclo da cultura e do uso de defensivos (BUXTON; PETTERSON; BRIGGS, 1979).…”
Section: Introductionunclassified
“…One concern with the UNRC system is that fiber quality may be sacrificed. Heitholt et al (1992) showed that narrow rows resulted in earlier canopy closure; while Buxton et al (1979) showed that narrow row spacings caused a greater percentage of fruit to be set earlier. Both of these factors, along with reduced boll size observed in high densities (Fowler and Ray, 1977), have the potential to negatively affect fiber quality.…”
mentioning
confidence: 99%